Integrated PjBL-STEAM Jigsaw on Critical Thinking and Creative Thinking of Students: A Biotechnology Study - Chtherine Pauline Salhuteru; Pamella Mercy Papilaya; Marike Muskita (Jurnal Penelitian Pendidikan IPA, 2025)
Critical and creative thinking are two different ways of thinking, but both are important in problem-solving and decision-making. The aim of this study is to determine: 1) The difference in students’ critical thinking skills on biotechnology material after the implementation of integrated PjBL-STEAM Jigsaw; and 2) The difference in students’ creative thinking skills in biotechnology after the implementation of integrated PjBL-STEAM Jigsaw. The results of statistical tests showed a difference in students’ critical thinking skills after the application of integrated PjBL-STEAM Jigsaw, in both the control group and the experimental group. Post-hoc tests revealed a significant difference in critical thinking between Pertiwi High School and SMAK Rehoboth Ambon in the experimental group. The post-hoc tests also showed a significant difference in creative thinking for the control group, with a significant difference between SMAK Rehoboth and SMA Pertiwi Ambon. In the experimental group, no significant difference in creative thinking skills was found. Teachers need to develop learning models that enhance students' critical thinking skills, and provide questions that reflect students' critical thinking abilities, which can help students improve both their critical and creative thinking. Future research should investigate the factors affecting the low critical and creative thinking abilities of students